Geometry and contact characteristics of torus involute gears. (April 2017) - Liu, Lei; Tan, Jingwen; Fang, Meijuan
Aimed at overcoming high sensitivity to machining or mounting error of line-contact conjugate surfaces, a novel torus involute gear drive is proposed which can compensate large axial misalignments and possess good meshing characteristics without lead correction. The torus involute gear is essentially a special spur gear with continuous shifting in the second order. Based on the processing principle of the torus involute gears, their mathematical models are established according to the corresponding imaginary rack cutter. In order to provide the approach to choose proper designing parameters, geometry characteristics of the torus involute gear are investigated: condition equations of tooth undercutting for a convex torus involute gear and tooth pointing for a concave torus involute gear are formulated utilizing the developed mathematical models, and the approach to checking tooth flank interference is provided. Contact characteristics of the gear set is studied through tooth contact analysis and finite element analysis. The simulated results produce useful information about tooth contact pattern, stress distribution, and transmission errors of the gear set.